Recent changes in monthly surface air temperature over Peru, 1964–2014 - Vicente-Serrano, S.M. (2018)
This study assessed changes in the maximum and minimum surface air temperatures across Peru during the period 1964–2014. For this purpose, we employed the most complete records of air temperature series that were also subjected to a rigorous quality control and homogenization protocol. Based on the homogenized series, we created a monthly gridded data set of maximum and minimum air temperatures at a 5 × 5 km grid spacing. The results suggest a general warming trend in surface air temperature across Peru, albeit with clear spatial and seasonal variation. Our results also reveal some differences in the detectable trends between maximum and minimum air temperatures. Maximum air temperature trends mainly increased during the austral summer (DJF), but cold season minimum air temperature trends showed an opposite pattern, with the strongest warming being recorded in the austral winter (JJA). In addition, maximum air temperature trends exhibited a clear elevation-warming dependency, with the strongest warming recorded at highly elevated sites. On the contrary, this dependency is weakened for minimum air temperature trends, as lower magnitudes of change and even a cooling trend were observed at high elevations during most months of the year. For mean air temperature trends, there are no clear spatial and temporal seasonal differences across Peru.